Gejala Klorosis Pada Kacang Tanah (Arachis hhypogaea) Pada Alfisol Kapuran Dan Upaya Menbgatasinya = Chlorotic symptom in groundnut (Arachis hypogaea) grown on a calcareous Alfisol and effort in correcting it - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2001)
Abstract The objectives of this research were to confirm the cause of the chlorosis symptoms, to determine the effect of S and P applications on Fe availability and its uptake by the plant, and to determine groundnut response to these application on a calcareous Alfisol. The experiment was carried out in the greenhouse from November 2000 to January 2001, using a calcareous Alfisol collected from Brondong, Lamongan (East Java). The soil pH and CaCO3 content were 7.6 and 22.81%, respectively. The treatments were laid out in a randomized complete design with three replications. The treatments consisted of two factors and these were rates of S and P applications. Four rates of P (0, 0.021, 0.042, 0.083 g P2O5/kg of soil), and five rates of S (0, 0.5, 1.0, 1.5, 2.0 g S/kg of soil) were applied 30 days before planting. The variety of groundnut (Arachis hypogaea) used was Singa, and the plants were harvested 42 days after planting. Plant parameters observed were plant height, shoot and root dry weight, chlorosis intensity score, chlorophyll content index, and concentration and uptake of Fe, P, Ca, and S. Soil parameters measured were soil pH, available Fe, CaCO3 content, available SO4=, and available P. The results showed that the chlorosis symptoms in groundnut grown on the calcareous Alfisol was primarily due to a low available SO4. Application of S up to 2 g/kg of soil increased available SO4% decreased soil pH varying from 0.1 to 0.2 units for each increment of 0.5 g S/kg added, decreased CaCO3 content by 0.6%, increased S and P concentrations in youngest fully matured leaf (YFML) and in the shoot to above the critical levels, but decreased Ca in YFML and shoot below the excessive^ level. However, S application did not increase Fe concentration in the YFML and in the shoot, but increased its uptake in both. Optimal rate of S was 1.5 g/kg of soil, arid at that rate, chlorophyll content index increased by 27%, chlorosis intensity became very low, and both shoot and root dry weight at 42 DAP increased by 82.5% and 24%, respectively. Application of P up to 0.083 g P2O5/kg of soil increased soil available P, but did not affect the plant parameters observed.